2015
DOI: 10.1021/acs.chemrestox.5b00270
|View full text |Cite
|
Sign up to set email alerts
|

Wood Smoke Particle Sequesters Cell Iron to Impact a Biological Effect

Abstract: The biological effect of an inorganic particle (i.e., silica) can be associated with a disruption in cell iron homeostasis. Organic compounds included in particles originating from combustion processes can also complex sources of host cell iron to disrupt metal homeostasis. We tested the postulate that (1) wood smoke particle (WSP) sequesters host cell iron resulting in a disruption of metal homeostasis, (2) this loss of essential metal results in both an oxidative stress and biological effect in respiratory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…Even though some studies have postulated that nanosized particles elicit their toxicity through similar mechanisms regardless of their chemical composition (Ghio et al, ), our previous studies have shown that there are large differences in the type and the extent of the toxicological response that particles from different heating systems or from different fuels exhibit (Kasurinen et al, , Tapanainen et al, ). These differences have been attributed to the solubility of the particles and the proportion of their organic versus their inorganic content.…”
Section: Discussionmentioning
confidence: 94%
“…Even though some studies have postulated that nanosized particles elicit their toxicity through similar mechanisms regardless of their chemical composition (Ghio et al, ), our previous studies have shown that there are large differences in the type and the extent of the toxicological response that particles from different heating systems or from different fuels exhibit (Kasurinen et al, , Tapanainen et al, ). These differences have been attributed to the solubility of the particles and the proportion of their organic versus their inorganic content.…”
Section: Discussionmentioning
confidence: 94%
“…A majority of studies to date investigating the toxicological impact of biomass smoke have used aqueous smoke extracts or smoke particulate-containing condensates to treat submerged cell cultures, while a few have used particulates collected from homes that use dung biomass for cooking and heating (6, 7, 4145). Here, we primarily exposed lung airway cells to whole dung biomass smoke at the air-liquid interface, and only used extracts when using non-airway reporter cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are the main cellular consumers of iron, and a number of vital cellular processes rely on precise mitochondrial iron regulation. Failure to correctly regulate mitochondrial iron leads to mitochondrial dysfunction, which is observed in response to wood smoke (loss of mitochondrial iron [107]) and CS (increased mitochondrial iron [33]). In mice, IRP2 deficiency protects against CS-induced COPD and CS-induced mitochondrial iron loading.…”
Section: Cellular Repercussions Of Abnormal Iron Homeostasis In Copdmentioning
confidence: 99%